2016
DOI: 10.1371/journal.pone.0159190
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Dyslexic and Non-Dyslexic Children in the Performance of Phonological Visual-Auditory Recognition Tasks: An Eye-Tracking Study

Abstract: The object of this study was to explore further phonological visual-auditory recognition tasks in a group of fifty-six healthy children (mean age: 9.9 ± 0.3) and to compare these data to those recorded in twenty-six age-matched dyslexic children (mean age: 9.8 ± 0.2). Eye movements from both eyes were recorded using an infrared video-oculography system (MobileEBT® e(y)e BRAIN). The recognition task was performed under four conditions in which the target object was displayed either with phonologically unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…A great variety of scientific studies have confirmed the presence of significant alterations in oculomotricity in children with neurodevelopmental disorders [ 4 , 5 , 6 , 7 , 31 , 32 , 33 , 34 , 35 ]. However, these altered oculomotor patterns are not specific to this type of disorders [ 4 ], as they are also present in healthy children, and they have the potential to affect reading [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A great variety of scientific studies have confirmed the presence of significant alterations in oculomotricity in children with neurodevelopmental disorders [ 4 , 5 , 6 , 7 , 31 , 32 , 33 , 34 , 35 ]. However, these altered oculomotor patterns are not specific to this type of disorders [ 4 ], as they are also present in healthy children, and they have the potential to affect reading [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty children with reading disorders (from 7.8 to 12 years old) were recruited from the Robert Debré Pediatric Hospital. The children in the study underwent a complete evaluation (see our previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Facoetti et al [ 7 ] reported also in children with dyslexia a specific disability in orienting as well as in sustained focusing visuospatial attention. Our group further explored oculomotor capabilities in dyslexic children and suggested a deficit in visual attentional processing in relation to the immaturity of cortical structures responsible for saccades triggering [ 8 , 9 , 10 ]. Reading, in fact, corresponds to a complex cognitive process during which several mechanisms are involved: visual perception, eye movements such as saccades and fixations, and semantic and linguistic abilities; consequently, a deficit in one of these different components could cause impairment in reading acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…A speech therapist, a psychologist and a pediatrician evaluated the conditions of these children and performed a diagnosis according to the DSM-5 diagnostic criteria [ 24 ]. According to previous studies, these children are expected to show oculomotor abnormalities in most of cases [ 17 , 18 , 19 , 20 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%